"You really could be something quite special": A qualitative exploration of athletes' experiences of being inspired in sport. (May 2016) - Figgins, Sean G.; Smith, Matthew J.; Sellars, Christopher N.; Greenlees, Iain A.; Knight, Camilla J.
Abstract: Objectives: The purpose of this research was to provide an explicit examination of inspiration in sport. In Study 1, we explored (a) what inspires athletes in sport, and (b) the consequences of being inspired. The aims of Study 2 were to explore (a) the contexts in which leaders inspired athletes, (b) leader behaviours and actions that inspire athletes, and (c) the consequences of being inspired by leaders. Design: Two qualitative descriptive studies were conducted in order to explore athletes' experiences of being inspired. Method: In Study 1, 95 athletes wrote about an experience of being inspired in sport. Study 2 utilised semi-structured interviews to explore 17 athletes' experiences of being inspired by leadership. Data were analysed via inductive thematic analysis. Results: In Study 1, athletes' responses revealed three sources of inspiration: personal performance, accomplishments, and thoughts; role models; and leadership. Findings from Study 2 indicated that athletes were inspired by a range of leadership behaviours (e.g., demonstrations of belief) in a variety of, mainly negative, situations (e.g., following poor performance). Broadly, findings from both studies revealed inspiration to impact on athletes' awareness of their capabilities, confidence, motivation, and behaviour. Conclusions: Overall, the findings indicate that an experience of inspiration can be evoked by a range of sources (most prominently leadership) and can have a powerful effect on athletes and their performance. Further research is required to understand how and why leaders can exert an inspirational impact on athletes. Highlights: Two studies examining inspiration in sport. Inspiration can be evoked by external sources in sport. Leaders are a major source of inspiration for athletes. Inspiration can change athletes' awareness of their capabilities. Inspiration can influence confidence, motivation and behaviour.